The Ninja: An Invented Tradition? - Stephen Turnbull (Journal of Global Initiatives, 2015)
The ninja is a well known phenomenon in Japanese military culture. The popularity of the tradition is centered on the neighboring areas of Iga and Kōka where ninja are a profitable tourist attraction. This paper examines the historical sources on which the ninja tradition is based to see if the pre-eminence claimed by Iga and Kōka is justified. It is shown that they were no different from several other places in their geography or their politics and that only one reliable account of secret warfare can be identified before 1581, the year when Iga Province ceased to exist as an independent self-governing entity. Secret warfare was practiced throughout Japan but this tiny area of Japan claimed a particular expertise in it and thereby invented a tradition that is still resonant today and now has all the hallmarks of a cult.